2012
DOI: 10.1088/1748-6041/7/6/065006
|View full text |Cite
|
Sign up to set email alerts
|

Impregnation of silver sulfadiazine into bacterial cellulose for antimicrobial and biocompatible wound dressing

Abstract: Silver sulfadiazine (SSD) is a useful antimicrobial agent for wound treatment. However, recent findings indicate that conventional SSD cream has several drawbacks for use in treatments. Bacterial cellulose (BC) is a promising material for wound dressing due to its outstanding properties of holding water, strength and degradability. Unfortunately, BC itself exhibits no antimicrobial activity. A combination of SSD and BC is envisaged to form a new class of wound dressing with both antimicrobial activity and bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 44 publications
6
44
0
Order By: Relevance
“…The BC membranes, which never dry, are highly nanoporous materials. That allows for drugs' incorporation into its structure, which will serve as a drug delivery system of controlled release and in the same time would serve as a physical barrier for environmental pathogens that may cause wound infection [38,75]. For example, such antimicrobial substance is benzalkonium chloride, which was incorporated in the BC by Wei et al Such dry BC film possessed good portability and good mechanical properties, as well as high water absorption capability.…”
Section: Drugs As a Solution For Poor Bc Antimicrobial Activitymentioning
confidence: 99%
“…The BC membranes, which never dry, are highly nanoporous materials. That allows for drugs' incorporation into its structure, which will serve as a drug delivery system of controlled release and in the same time would serve as a physical barrier for environmental pathogens that may cause wound infection [38,75]. For example, such antimicrobial substance is benzalkonium chloride, which was incorporated in the BC by Wei et al Such dry BC film possessed good portability and good mechanical properties, as well as high water absorption capability.…”
Section: Drugs As a Solution For Poor Bc Antimicrobial Activitymentioning
confidence: 99%
“…1,2 For many medical procedures to remain viable treatments, novel therapeutic approaches to infections need developing in order to guarantee sufficient protection against pathogens. The use of metals, predominantly silver, in the form of salts or nanoparticles is a well-established antimicrobial strategy that found applications in creams, 3 wound wrappings, 4 fabrics, 5 and eluting surfaces. [6][7][8] However, concerns regarding the use of silver are growing, particularly its long-term safety linked to accumulation in the environment and the body, 9,10 hence other antimicrobial agents are in urgent need.…”
Section: Introductionmentioning
confidence: 99%
“…31 It is reported that BC has free hydroxyl groups that impart a weak positive surface charge. 32 Considering all these properties, we aimed at the preparation of nanocomposite scaffolds (BC-HA and BC-GAG) mimicking the bone and the cartilage tissue to be repaired. For the preparation of BC-HA nanocomposites, the obvious choice was an optimal biomimetic mineralization synthesis approach employing SBF for the deposition of HA.…”
Section: Discussionmentioning
confidence: 99%